Product portfolio management based on product life cycle - Pererva, P. G.; Matrosova, Viktoriya; Dіakova, Natalia (My University, 2022)
It is proven that the research of product renewal processes should be based on the concept of the life cycle of products directly in production, which covers the period from the beginning of development to the removal of an outdated model from industrial production due to its commercial impracticality.
Keywords: product portfolio; management; life cycle; industrial enterprises; innovations